2016
DOI: 10.1039/c6cc06990h
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into sodium storage in hard carbon anodes using local structure probes

Abstract: OperandoNa solid-state NMR and pair distribution function analysis experiments provide insights into the structure of hard carbon anodes in sodium-ion batteries. Capacity results from "diamagnetic" sodium ions first adsorbing onto pore surfaces, defects and between expanded layers, before pooling into larger quasi-metallic clusters/expanded carbon sheets at lower voltages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
262
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(290 citation statements)
references
References 18 publications
27
262
1
Order By: Relevance
“…Indeed, the validity of the mechanism was provedb y several experimental studies. [35] The XRD PDF analysis was also performed and it was concluded that micrographiticd omains of pristine hard carbonsw ere comprised of curved graphene sheetsw hichm ade the interplanar separation dependento nt he penetration vector, r,r ather than being as ingle-value parameter throughout the crystallite. [31] Their arguments were supported by the decrease in the SAXS intensity ( Figure 5) from the nanoporousr egion,o wing to their filling by sodium.T he same authors also reportedashift of the (002) graphitic peak to lower 2q valuesi mmediately after completion of the sloping region, with no further change in the low-voltage region ( Figure 6).…”
Section: Mechanism Of Sodium Storagei Nhard Carbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the validity of the mechanism was provedb y several experimental studies. [35] The XRD PDF analysis was also performed and it was concluded that micrographiticd omains of pristine hard carbonsw ere comprised of curved graphene sheetsw hichm ade the interplanar separation dependento nt he penetration vector, r,r ather than being as ingle-value parameter throughout the crystallite. [31] Their arguments were supported by the decrease in the SAXS intensity ( Figure 5) from the nanoporousr egion,o wing to their filling by sodium.T he same authors also reportedashift of the (002) graphitic peak to lower 2q valuesi mmediately after completion of the sloping region, with no further change in the low-voltage region ( Figure 6).…”
Section: Mechanism Of Sodium Storagei Nhard Carbonsmentioning
confidence: 99%
“…The carbon microtubules synthesized at1 300 8C( HCT-1300) had ac ontribution of 115mAh g À1 from the sloping region to the total ca- Figure 5. [35].) a) SAXS profile of the fresh electrode, ready to discharge.…”
Section: Storage-capacity Relationshipmentioning
confidence: 99%
“…The two electrochemical processes of a sloping region followed by a process close to 0 V vs. sodium suggest that sodium insertion proceeds via a two‐stage mechanism associated with the two electrochemical signals: intercalation of sodium between nearly parallel layers, followed by the formation of metallic species within the pores of the material at low voltages . To explore the proposed mechanisms, X‐ray total‐scattering PDF analysis was used to study local structures for Na insertion in the higher‐ and lower‐voltage processes, and the results are shown in Figure a . A differential PDF, where the PDF for the pristine carbon is subtracted from the PDF at various points in the discharge, highlights additional interactions present on the insertion of sodium: samples discharged to 300 mV and 180 mV along the sloping region show only minor features at very low r (<7 Å).…”
Section: Novel Methods For Sodium‐ion Battery Materialsmentioning
confidence: 99%
“…Weaker peaks are a result of minor changes to the carbon structure and termination ripples. Reproduced with permission . Copyright 2016, The Royal Society of Chemistry.…”
Section: Novel Methods For Sodium‐ion Battery Materialsmentioning
confidence: 99%
“…Their second observation was that the capacity corresponding to the sloping voltage region decreases after thermal treatment (see Figure 6e) together with the amount of local defects as deduced from Raman, without increasing the degree of graphitization, as no significant change of the interlayer distance was observed. [52] Moreover, two previously reported experimental studies based on in situ small-angle X-ray scattering (SAXS) [52] and ex situ 23 Na nuclear magnetic resonance (NMR) [56,58] converge in concluding that the low voltage plateau is associated with an insertion of sodium into the fine structure pores of the hard carbon in an intermediate oxidation state between Na + and Na metal. It is a quite puzzling result given that a previous report of ex situ X-ray diffraction patterns performed at various states of charge in hard carbon show that the interlayer distance already increases upon oxidation during the sloping voltage region below 1 V (see Figure 6c), [25] and more significantly than during the low voltage plateau, which is also confirmed by the shift of the G band in the Raman spectra.…”
Section: Charge Storage Mechanismsmentioning
confidence: 95%